Benzene adsorption on a pseudomorphic Cu monolayer on Ni(111) - a combined TPD and ARUPS study - Koschel, Herbert; Held, Georg; Trischberger, P.; Widdra, Wolf; Steinrück, Hans-Peter (Surface Science, 1999)
The adsorption and desorption of benzene on a pseudomorphic Cu monolayer on Ni(111) has been investigated by temperature programmed desorption (TPD) and angle-resolved ultraviolet (UV) photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation. The experimental results are compared to those of an earlier investigation of benzene adsorbed on Ni(111). Benzene is weakly chemisorbed on the pseudomorphic Cu monolayer on Ni(111): Desorption of the first layer occurs in the temperature range between 155 and 230 K with no sign of dissociation; the analysis of the binding energies of the molecular benzene levels reveals small bonding shifts of 0.2-0.30 eV of the benzene π levels as compared to 1.4 eV for the strongly chemisorbed saturated benzene layer on Ni(111). The orientation of benzene on Cu/Ni(111) is determined from the ARUPS spectra in combination with symmetry selection rules. For low coverages, the molecular plane is oriented parallel to the surface, as is also the case for benzene on Ni(111). However, no well defined azimuthal orientation is observed, which is attributed to frustrated rotations and/or the high mobility of the adsorbed molecules at the temperature of investigation (80 K). For the saturated first benzene layer on Cu/Ni(111), a tilting of the adsorbed molecules occurs due to lateral interactions.